Sosialisasi Pencegahan Penyakit Demam Berdarah di Desa Markanding Kabupaten Muaro Jambi - Kusuma, Ahmad; Fadhel, Denny; Putri, Raya Cahyani (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this service activity is to provide education to the public about the dangers of dengue fever. The service method used is: 1) the first stage is to notify the administrators of the Al-Ishlahut Tholibin Musholla to convey an appeal via loudspeaker about the dangers of dengue fever, as well as provide an announcement regarding the socialization of the prevention of dengue fever; 2) the second stage is lecture and question and answer. The lecture was held to disseminate information about the epidemic, eradication and control of dengue fever; 3) the third stage is attaching brochures appealing or warning about the dangers of dengue fever to residents; and 4) the fourth stage asked the hamlet head to convey an announcement to each hamlet, because in Markanding Village, Bahar Utara District, Muaro Jambi Regency there are 6 hamlets, so each hamlet made a schedule for morning exercise so that the body becomes healthy and fit. Based on the activity process, it can be seen that the participants were very enthusiastic in taking part in the activity. The participants asked that this activity be carried out regularly so that they could increase their knowledge and insight in the fields of environmental health and infectious diseases. All material was presented well and was well received and understood by the participants.